Integración interinstitucional, un medio para la dinamización de la internacionalización productiva (2022)
The present research makes a diagnosis that determines the scope and competence of interinstitutional articulation in increasing exports and boosting the exportable supply, given the low levels that the department of Tolima currently has in terms of productive internationalization. According to the preceding, the diagnosis is carried out under a qualitative study with a descriptive approach, since it characterizes the institutional profiles and its offers of plans, programs and projects to the productive sector